The relationship between medications adherence and quality of life among patients with type 2 diabetes in Hospital Pakar Universiti Sains Malaysia. - Afandi, Nur Sabrina (Universiti Sains Malaysia, 2024)
Diabetes mellitus is a chronic disorder that affects the body's ability to utilize blood glucose, a vital source of energy for cells. This study aims to study the relationship between medication adherence level, and quality of life among type 2 diabetes mellitus patients in Hospital Pakar USM.The study is conducted in outpatients settings, and 84 participants were recruited via purposive sampling. Medical compliance questionnaire is given out to assess patients' adherence to prescribed medical regimens while diabetes quality of life questionnaire consists of 3 domains, which are satisfaction, impact and worry. Results revealed that most respondents are aged of 51 to 70 years old (60.7%), male (54.84%),Malays (94.0%), secondary education level (65.5%), married (91.7%) with salary more than RM1000 (86.9%).In addition , results also revealed that majority of participants had suffered from T2DM for about 5 to 10 years (60.7%),undergo monotherapy treatment (65.5%),experience comorbidities (82.1%) and taken less than 3 medication (92.9%). The study demonstrates a statistically significant moderate negative correlation (r = -0.469, p < 0.01) between medical compliance and quality of life among 84 respondents. This suggests that lower medication compliance (higher MCQ Total scores) correlated with lower diabetes-related quality of life (lower Tota lDQOL scores). The significance level (p = 0.000) indicates that this link was unlikely to arise by coincidence. The difference in QoL between the non-adherent and adherent groups is statistically significant. This shows that adherence to the regimen or therapy under study may be related with a worse QoL. However, further investigation is required to confirm and identify other factors that may also contribute this present finding.